PENINGKATAN PEREKONOMIAN KELUARGA MELALUI KETRAMPILAN WANITA GRIYA UKM CINERE DEPOK - Tati Handayani; Rosali Sembiring Colia; Heni Nastiti; Yudi Nur Supriadi (Jurnal Abdimas Bina Bangsa, 2023)
Mitra is the Cinere UKM griya which is a group of SMEs consisting of 156 SME members from Gandul village. Cinere, Pangkalan Jati and Pangkalan Jati Baru which have businesses in the fields of Culinary, Handy Craft, Fasion and Services. During the Covid-19 pandemic, SMEs experienced various problems, including facing a decrease in productivity which resulted in a significant decrease in profits, because many activities could not be done before the pandemic, therefore the service offered to make creativity from acrylic materials as an alternative to increase product variations to be sold. For this reason, training and assistance are needed in making flowers, assesories from acrylic materials. The purpose of carrying out service at the Cinere UKM griya is to provide training and assistance to Cinere SMEs, especially women to make flowers and assesories from beautiful and attractive acrylic raw materials, so that they can be an alternative to increase product variations for sale